Resveratrol protects against high glucose-induced steroidogenesis and apoptosis in murine granulosa cells: Resveratrol guards granulosa cells from glucose-induced damage - Zhang, Ning; Shan, Yinghua; Lian, Huayu; Ma, Xinheng; Zhang, Wei; Liu, Xiaoyan; Zhuang, Lili; Liu, Xianna; Liu, Yun; Zheng, Kexin (Cellular and Molecular Biology, 2023)
Resveratrol (Res) is a polyphenolic compound that exhibits a diverse array of biological effects. Herein, we detected the ability of Res on murine granulosa cells (GCs) against impaired steroidogenesis and apoptotic death in response to high glucose levels. Ovarian GCs were harvested from C57BL/6 mice and cultured in steroidogenic media supplemented with follicle-stimulating hormone (FSH, 30 ng/mL), Res (50 μmol/L), and low or high glucose concentrations (5 mM or 30 mM). After culture for 24 h, cell supernatants were harvested and the levels of progesterone and estradiol therein were measured. Also, caspase-3 activity and the expression of genes associated with apoptosis and steroidogenesis were assessed. High-glucose treatment suppressed steroidogenesis in this assay system, resulting in the impaired expression of steroidogenesis-related genes including Cyp11a1, Cyp19a1, 3βHSD, and StAR and a concomitant decrease in progesterone and estradiol production. Cells exposed to high glucose also exhibited apoptotic phenotypes characterized by Bax upregulation, Bcl-2 downregulation, and increased caspase-3 activity levels. However, Res treatment was sufficient to reverse this high glucose level-induced apoptotic and steroidogenic phenotypes with improving progesterone and estradiol production, and these maybe related the effects of Res on Cyp11a1, Cyp19a1, 3βHSD, and StAR expressions. These data suggested that Res is well suited to overcoming the negative effects of hyperglycemia of GC functionality.